Práticas integrativas e complementares na atenção primária à saúde em João Pessoa-PB - Ferreira, Bruno Wesley Ramalho Cirilo (2023)
The study aimed to understand and evaluate the offer, work and continuing education around Integrative and Complementary Practices (PIC), from the perspective of health professionals in Primary Health Care (PHC) in a capital in northeastern Brazil. In the quantitative stage, a cross-sectional study was developed, with analysis of modules I and II of the 3rd Cycle of the National Program for Improving Access and Quality of Primary Care. 186 health professionals were interviewed considering the five health districts of a northeastern capital. Of these, 88.7% offered some practice, with nurses offering the most (96.2%). Auriculotherapy (83.3%), the use of medicinal plants and herbal medicines (77.9%) and community therapy (48.9%) were the practices most offered. 86.5% of respondents reported receiving managerial support, however, there was a shortage of inputs, in which seeds or crystals for auriculotherapy (56.7%), plant drugs (15.2%), compounded herbal medicine (12, 5%) or industrialized (4.1%) were not available in sufficient quantities. 82.2% of respondents participated in permanent education moments related to practices offered by municipal management (93%) at the health unit itself (90.8%). In the qualitative stage, interviews were conducted with PHC professionals. Data collection was performed from semi-structured interviews. To Among the interviewees, 11 were female and 1 male. The most present professional category was nursing (4), followed by dentists (3), social workers (2), physiotherapists, psychologists and physical educators (1). From the thematic analysis, four units of analysis and seven thematic categories emerged, perception of PIC in health care, work process and change in health care production, work process and change in care production, conflict of models of care health care: "goals-centered" service and comprehensive perspective, Visibility of PICs: registration in users' records, management and support in offering PICs: strengths and weaknesses, Permanent education in Health with a focus on PICs: offer involving the various actors of the PICs APS and Offer of PICs in the APS and the pandemic period. It was observed, on the one hand, the offer of PIC in the municipality, however, improvements are needed in the management of the work process, of inputs, managerial support, permanent health education aimed at qualifying and expanding the offer of different PICs in PHC.